MELALUI MANAJEMEN USAHA KESEHATAN SEKOLAH, SMP NEGERI 36 PALEMBANG MENDAPAT PREDIKAT SEKOLAH SEHAT TINGKAT KOTA - Asneti, Asneti; Restianey, Fenti; N, Kartini Dewi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
School Health Effort is part of the substance of special service management that is engaged in school health. Special service management in schools is basically carried out to support learning and can meet the special needs of students in school. This study aims to find out how to plan, organize, implement, supervise School Health Effort in SMP Negeri 36 Palembang. The research method used is a qualitative method with a descriptive case study design. The unit of analysis is SMP Negeri 36 Palembang. Data was taken by purposive sampling through in-depth interviews and document searches. Data analysis with explanation building is the technique of explaining the results of interviews and document tracking. The results of the study show that the School health planning in SMP Negeri 36 Palembang has been well structured, follows the UKAC POAC standard and already has a Moment of Understanding (MOU) with related parties namely the Puskesmas and there is a clear funding system. The Organizational Structure in SMP Negeri 36 Palembang has followed the UKS POAC standard which consists of the structure of the parent organization and sub-structure of the organization, namely the implementing organization and school health business organization as the parent organization and the jumantik organization as sub-organizational structures. The form of supervision of the School Health Effort in the SMP Negeri 36 Palembang was carried out in coordination with the puskesmas and evaluating activities.